Analisis Pemanfaatan Internet Mahasiswa untuk Meningkatkan Literasi Informasi Masyarakat di Era Revolusi Industri 4.0: Analysis of Students' Internet Utilization to Improve Public Information Literacy in the Industrial Revolution Era 4.0 - Sri Nurhayati; Safuri Musa (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
This research aims to determine the level of information literacy, internet utilization as a source of information literacy, and internet utilization to increase student reading interest at Institut Keguruan dan Ilmu Pengetahuan Siliwangi (IKIP Siliwangi). This research uses qualitatif descriptive method. Data were collected using questionnaires, interviews, and documentation studies. Selection of research subjects using the snowball sampling technique. This research's subjects consisted of 23 students related to literacy, 16 students related to information literacy, 18 students related to the results of internet utilization in increasing students' reading interest, and 1 lecturer of Community Education at IKIP Siliwangi. The results showed that students 'understanding of information seeking and information selection was still low compared to students' understanding of information dissemination. Students are still not optimal in using information literacy. Only a few students understand information literacy, how to use information literacy, and select information. Students understand the use of the internet and use it only for social media activities, but low in utilizing the internet as a learning source. Also, the results of the study indicated that students' reading interest was low. Students choose to use the internet instead of reading books. Students do not feel the need to come to the library to find books that match what they need to learn. Therefore, students have to understand the concept of information literacy and take advantage of various applications that support learning.